2011
DOI: 10.1111/j.1475-6773.2011.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Safety Net of Specialty Care for the Uninsured: A Case Study

Abstract: Objective. To describe core principles and processes in the implementation of a navigated care program to improve specialty care access for the uninsured. Study Setting. Academic researchers, safety-net providers, and specialty physicians, partnered with hospitals and advocates for the underserved to establish Project AccessNew Haven (PA-NH). PA-NH expands access to specialty care for the uninsured and coordinates care through patient navigation. Study Design. Case study to describe elements of implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In our community of New Haven, Connecticut, we established in 2009 a volunteer specialty-physician network that donates medical care in partnership with hospitals and local community organizations for uninsured patients with urgent medical needs. 5,6 Patients identified at our student-run free clinic with urgent specialty care needs are referred to a specialist who provides medical care at no charge to the patient in the specialist's own office. 7 Although not a panacea for lack of insurance, voluntary physician networks and free clinics are widespread in the United States and help to shore up the safety net in local communities.…”
Section: Strategies For Providing Care In Resource-poor Settingsmentioning
confidence: 99%
“…In our community of New Haven, Connecticut, we established in 2009 a volunteer specialty-physician network that donates medical care in partnership with hospitals and local community organizations for uninsured patients with urgent medical needs. 5,6 Patients identified at our student-run free clinic with urgent specialty care needs are referred to a specialist who provides medical care at no charge to the patient in the specialist's own office. 7 Although not a panacea for lack of insurance, voluntary physician networks and free clinics are widespread in the United States and help to shore up the safety net in local communities.…”
Section: Strategies For Providing Care In Resource-poor Settingsmentioning
confidence: 99%
“…We expect social safety net activation should matter more for patients' use of specialty care than for primary care as cost is not the driving factor due to free clinics increasingly offering a range of services at low or no cost to the patients (Darnell 2011;Hall 2011;Johnson 2010;Spatz et al 2012;VanderWielen and Ozcan 2015). By identifying these two indicators of a social safety net, we gain a better understanding of not only if networks matter but also how broader activation of a social safety net may warrant further inquiry.…”
Section: The Role Of Social Networkmentioning
confidence: 99%
“…We further break down specialty care services by physical specialty care services (a physical ailment or issue is addressed) and behavioral specialty care services (a mental health issue is addressed or health education is sought out). Research indicates that for the uninsured, the combination of sporadic primary care with even more limited access to specialty care remains a central challenge (Hadley 2003;Shi 1995;Spatz et al 2012). In the case of specialty care, Katharine E. Zuckerman et al (2013) find in their study that the most frequent barriers for patients involved personal work obligations, childcare, and transportation constraints while barriers to the clinic included the process for making appointments and the availability of care.…”
Section: Diversity and Complexity Of Health Care Servicesmentioning
confidence: 99%
“…For instance, Spatz et al. () have taken a proactive role in translating research that demonstrated barriers to access to specialty care into policy‐based solutions for those barriers. They describe the formation of a team in New Haven, which worked with Project Access to create a partnership of providers, advocates, and researchers, to identify and overcome challenges to obtaining specialty care.…”
mentioning
confidence: 99%